Pengembangan Perangkat Pembelajaran IPA Berbasis Guided Inquiry - Nur’aini, Nur’aini; Danial, Muhammad; Sugiarti, Sugiarti (Chemistry Education Review (CER), 2020)
This study is development research, which aims at producing guided inquiry-based IPA (Natural Sciences) learning tools in energy and life system subject which is valid, practical, and effective, discovering the level of validity, practicality, and effectiveness of guided inquiry-based IPA learning tools in energy and life system subject developed. The development of learning tools employed Thiagarajan (Four-D) model which consists of four stages, namely defining, design, development, and dissemination. The test of learning tools was conducted to the students of grade VII.1 at SMPN 36 Makassar of academic year 2018/2019. Data collecting employed observation sheet and questionnaire. The data were then analyzed by using descriptive analysis technique. The products produce in this study are the lesson plan (RPP), student’s worksheet (LKPD), and student’s textbook (BAPD). The results of the validation on the learning tools developed, it is obtained the mean score based on the assessors which met the valid criteria and all of the components of learning tools are valued as reliable. The result of the field test on the practicality of learning tools developed shows that there is consistency between the result of experts’ perceptions and observers’, which is both gave high criteria or good. The learning tools are also effective to be applied because the result of the field test indicates that there is consistency between the result of experts’ perceptions and observers’. The result of experts perceptions gave the effectiveness result with high criteria or good. The result of observation on four indicators of effective criteria were all met.